If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P + -18 = 45 Reorder the terms: -18 + P = 45 Solving -18 + P = 45 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + P = 45 + 18 Combine like terms: -18 + 18 = 0 0 + P = 45 + 18 P = 45 + 18 Combine like terms: 45 + 18 = 63 P = 63 Simplifying P = 63
| h+1.6=5.09 | | 3(sin(X))=cos(X) | | 4-4tan^2x=0 | | 2x-3-5=8 | | D+20=2.5 | | 8lnx=7 | | 8x^2-34x-9=0 | | 3.5=z/3 | | 5m-3(-7m+4)= | | 7x+10=100 | | k+13.63=15.63 | | 3x+4=2x+18 | | x-(0.2*x)=10000 | | f+1=3 | | K-14=12 | | (5x-26)x=63 | | 3(r-5)=13 | | c+20=35 | | 5m-16-8m=23 | | -6u^2-11u-4=0 | | 1.42=s-2.88 | | 9m-5(-2m+9)= | | 9m-5(-2+9)= | | 5y-16-8y=23 | | 3+2x=6+x | | 7m^2+14m-7=0 | | x=-5-2i | | (1/5)x-2-1= | | t/4=4.4 | | .5714285714x-13=.8571428571 | | 6(3z-1)-3(z+3)=4(z+1) | | (3.8+x)(2.5+x)=78.25 |